2003
DOI: 10.1046/j.1365-2222.2003.01515.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of alcohol consumption to total immunoglobulin E and the development of immunoglobulin E sensitization: the Copenhagen Allergy Study

Abstract: This epidemiological study confirms that alcohol consumption has an influence on levels of serum total IgE. A significant association between alcohol consumption and the development of IgE sensitization was not established. However, there seems to be a lack epidemiological data on this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
88
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 30 publications
(49 reference statements)
11
88
1
3
Order By: Relevance
“…smoking and alcohol a pattern that was also similar to the pattern reported elsewhere: allergen-specific IgE levels were increasing with alcohol consumption 24 and were decreased among smokers. 25 A major strength of our study, in addition to the large numbers of cases and controls, is the careful assessment of atopy by specific IgE measurement.…”
Section: Discussionsupporting
confidence: 87%
“…smoking and alcohol a pattern that was also similar to the pattern reported elsewhere: allergen-specific IgE levels were increasing with alcohol consumption 24 and were decreased among smokers. 25 A major strength of our study, in addition to the large numbers of cases and controls, is the careful assessment of atopy by specific IgE measurement.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our findings, few other studies have found a relation between alcohol abuse and raised total IgE [10,[20][21][22]. A recent Korean study showed an increased prevalence of allergic sensitization to house dust mite in alcoholics [20].…”
Section: Resultssupporting
confidence: 92%
“…A recent Korean study showed an increased prevalence of allergic sensitization to house dust mite in alcoholics [20]. There are few other studies also suggesting an association between increased IgE and allergic sensitization in alcoholics [22][23][24]. In control subjects who showed high total IgE levels (>500 IU/ml), specific IgE levels were measured against common allergens (house dust, tree, and food allergens) to detect an allergic component.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, alcohol beverages consumption has been associated with increased risk for asthma and hay fever symptoms, allergic sensitization and serum IgE (45)(46)(47). The aMED score, used in the present study, considers total ethanol intake, irrespective of the different alcoholic beverages.…”
Section: Discussionmentioning
confidence: 98%